ANALISIS PENGARUH BEBERAPA DOSIS PUPUK BOKASHI KOTORAN AYAM TERHADAP PERTUMBUHAN DAN PRODUKSI TIGA VARIETAS TOMAT (Lycopersicum esculentum MIIL.) DI DESA AIRMADIDI - Marthinus Marcus Sahetapy; Jantje ., Pongoh; Wenny ., Tilaar (AGRI-SOSIOEKONOMI, 2017)
Objectives of the study were to determine the effects of the several dosage of bokashi live stock fertilizer on growth and yield of three varieties of tomatos as well as the interaction between both factors. This research was conducted in October 2016 until February 2017 in experimental garden of Faculty of Agriculture Universitas Klabat Airmadidi Manado. The research conducted from October 2016 to February 2017. Factors studied were 1) types of bokashi fertilizer, consisted of 4 levels: dosage 10 ton in ha, 15 ton in ha, 20 ton in ha and 25 ton in ha manure and 2) varieties of tomatoes, consisted of three types: Tantyna F1, Tombatu F1 and Betavila F1. Variables observed were (1) growth variables consists of plant height, stem diameter, leave numbers at ages 30, 40, 50 and 90 days after transplanting (DAT), flower numbers, brance production numbers and bunches fruit numbers at ages 30, 40 and 50 days after transplanting (DAT), (2) yield variables consists of fruit numbers, fruit weight and fruit diameter for 5 times of harvest at age 60, 65, 70, 75 and 80 days after transplanting (DAT). The experiment was designed factorially in a randomized block design with three plants as replicates. Data were analyzed by multiform analysis and continued with 5% BNJ.The research showed that the best plant growth was found at the combination of varietas betavila F1- chicken manure, it means the best growth were found at Betavila F1 varietas.